2002
DOI: 10.1590/s0102-86502002000900019
|View full text |Cite
|
Sign up to set email alerts
|

Led enhancement in mitochondrial oxidative phosphorylation for hepatectomized rats

Abstract: Recently, the LED (light emitting diode) developed by the Optics Group of IFSC-USP has been used instead of laser for the treatment of skin tumors by the PDT (Photodinamic Therapy) because of its low operational cost compared to the use of a laser. In this paper we investigate the effect of LED light on oxidative phosphorylation during liver regeneration after partial hepatectomy. Twenty-four male Wistar rats (250 g) were kept in identical housing units on a 12-hour light/12 hour dark cycle. The LED 10 group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Considering that AST is located predominantly in the mitochondria, the present results may suggest that part of the beneficial effects of LLLT on liver function could be attributed to improved mitochondrial function. In line with this concept, previous studies have shown that LLLT and LED therapy may improve mitochondrial function in hepatectomized rats . The fact that LLLT reduced the levels of liver enzymes such as AST, AP, GGT and LDH and also the total protein and globulin levels is extremely relevant and points out the possible mechanism of action of LLLT in CCl 4 ‐induced hepatic cirrhosis.…”
Section: Discussionmentioning
confidence: 66%
“…Considering that AST is located predominantly in the mitochondria, the present results may suggest that part of the beneficial effects of LLLT on liver function could be attributed to improved mitochondrial function. In line with this concept, previous studies have shown that LLLT and LED therapy may improve mitochondrial function in hepatectomized rats . The fact that LLLT reduced the levels of liver enzymes such as AST, AP, GGT and LDH and also the total protein and globulin levels is extremely relevant and points out the possible mechanism of action of LLLT in CCl 4 ‐induced hepatic cirrhosis.…”
Section: Discussionmentioning
confidence: 66%
“…A terapia com LED de baixa intensidade tem sido reportada como análoga da TLBI 8 , pois exerce efeito sobre a microcirculação, levando a uma vasodilatação 9 . Ocorrendo a vasodilatação, a quantidade de plasma que migra para o interstício é maior, deixando o sangue mais viscoso, o que torna a circulação mais lenta 10 .…”
Section: Introductionunclassified